Analisis Pengendalian Persediaan Bahan Baku Sepatu Kulit dengan Menggunakan Metode Material Requirement Planning (MRP) - Muhammad Fahri Azmi; Nabila Yudisha; Rahmad Rezeki (LPPM IAI Nasional Laa Roiba Bogor, 2023)
Raw material inventory control is a company policy that dappat control the inventory of raw materials with a balanced. Because raw material inventory is one of the factors in the production process, a shortage of raw materials will result in production delays, and conversely an excess of raw materials will result in increased storage costs and other costs. The purpose of this study was to determine and analyze the control of raw material inventories applied by MSMEs Chaniago Jaya. The type of research used is quantitative. Data sources in this study were obtained directly from the company. And the method used is MRP, the results showed that the application of the MRP method on the company lower cost when compared with the method that has been applied by the company, where the MRP method obtained a value of Rp 7,360,696 while the company Method obtained a value of Rp 11,427,675 with a difference of Rp 4,066,979. Keywords : Demand, raw material inventory, leather shoes manufacturing